Fostering Adversity Intelligence Among Students in Higher Education - Zubaedi Zubaedi (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study explores the significance of adversity quotient (AQ) in education and provides strategies to develop AQ as a critical life skill for students. AQ refers to an individual’s ability to endure and overcome challenges by transforming their mindset and actions when confronted with adversity. The research focuses on understanding how AQ can shape student behavior and enhance academic and personal growth. Methodology: A qualitative descriptive method with a phenomenological approach was employed in this study. Primary and secondary data were collected through observations, in-depth interviews, and documentation. Data were analyzed to identify patterns and factors influencing AQ development in educational contexts. Main Findings: The study identifies seven key factors influencing AQ in students: competitiveness, creativity, risk-taking, self-improvement, perseverance, study habits, and adaptability. The findings also highlight a four-step process for improving AQ: (1) Listen—assess responses to adversity, (2) Explore—analyze the root causes and consequences of challenges, (3) Evaluate—examine evidence critically, and (4) Act—implement solutions proactively. The research underscores the importance of fostering AQ to help students navigate academic difficulties, enhance problem-solving skills, and build resilience in various contexts. Novelty/Originality of the Study: This study introduces a specialized educational model for developing students' adversity intelligence, integrating AQ with soft skills and entrepreneurial competencies. It provides insights into AQ’s role in academic performance, mental well-being, and life skills. Additionally, it investigates the relationship between AQ and entrepreneurial ability, positioning adversity intelligence as a cornerstone for holistic student development in modern education.